Tribulus terrestris L.: a medicinal plant with promising therapeutic potential for skin diseases - Wang, Xiao-Mu; Liu, Xiao-Min; Zeng, Yan; Zhu, Ke-Jing; Shen, Tian-Tian; Bian, Fang (Frontiers in Pharmacology, 2026)
Tribulus terrestris L. (T. terrestris L.), a traditional medicinal plant, has garnered increasing attention for its potential in treating skin disease. This review comprehensively summarizes current research on the protective effects of T. terrestris L. in skin diseases. T. terrestris L. contains various bioactive metabolites, including steroidal saponins, flavonoids and alkaloids. These metabolites exhibit anti-inflammatory, antioxidant, antibacterial properties, and tyrosinase-regulating effects, making T. terrestris L. a promising candidate for treating multiple skin disorders. Studies have shown its potential efficacy against conditions such as atopic dermatitis, acne, and vitiligo. However, several limitations remain: its precise mechanisms of action in skin diseases are not yet fully elucidated, its standalone efficacy for complex skin diseases may be limited, and there is a lack of high-quality, large-scale clinical trials to conclusively verify its efficacy and safety. In conclusion, current evidence suggests T. terrestris L. has significant promise for the treatment of skin diseases. Future research should focus on conducting rigorous clinical trials, exploring combination therapies with conventional treatments, and deepening the investigation into its active components and mechanisms to expand its application in skin diseases.